Phraseological and linguistic elements widely used in German linguistics - Asrayev Sadriddin G'ulom o'g'li (Zien Journals, 2022)
This article describes linguistic and phrases and jargons, which are widely used in German speech
Keywords: Jargon; phrase; argots; layer